Early angiography in elderly patients with non-ST-segment elevation acute coronary syndrome: The cardio CHUS-HUSJ registry. (15th March 2022) - González Ferrero, Teba; Álvarez Álvarez, Belén; Cordero, Alberto; Martinón Martínez, Jesús; Cacho Antonio, Carla; Sestayo-Fernández, Manuela; Bouzas-Cruz, Noelia; Antúnez Muiños, Pablo; Casas, Charigan Abou Jokh; Otero García, Óscar; Arias, Federico García-Rodeja; Pérez Dominguez, Marta; et al.
ABSTRbstract: Background: In elderly patients with non-ST elevation acute coronary syndrome (NSTEACS), while routine invasive management is established in high-risk NSTEACS patients, there is still uncertainty regarding the optimal timing of the procedure. Methods: This study analyzes the association of early coronary angiography with all-cause mortality, cardiovascular mortality, heart failure (HF) hospitalization, and major adverse cardiovascular events (MACE) in patients older than 75 years old with NSTEACS. This retrospective observational study included 7811 consecutive NSTEACS patients who were examined between the years 2003 and 2017 at two Spanish university hospitals. There were 2290 patients older than 75 years old. We compared their baseline characteristics according to the early invasive strategy used (coronarography ≤24 h vs. coronarography >24 h) after the diagnosis of NSTEACS. Results: Among the study participants, 1566 patients (68.38%) underwent early invasive coronary intervention. The mean follow-up period was 46 months (interquartile range 18–71 months). This association was also maintained after propensity score matching: early invasive strategy was significantly related to lower all-cause mortality [HR 0.61 (95% CI 0.51–0.71)], cardiovascular mortality [HR 0.52 (95% CI 0.43–0.63)], and MACE [HR 0.62 (CI 95% 0.54–0.71)]. Concusions: In a contemporary real-world registry of elderly NSTEACS patients, early invasive management significantly reduced all-cause mortality, cardiovascular mortality, and MACE during long-term follow-up. Brief summary: In this real-world retrospective observational study that included 2451 patients older than 75 years old, 1566 patients (68.38%) underwent early invasive coronary intervention. After performing a propensity score matching, the early invasive strategy was still associated with lower all-cause mortality [HR (hazard ratio) 0.61, 95% CI (95% confidence interval) (0.51–0.71)], cardiovascular mortality [HR 0.52 (95%CI 0.43–0.63)], and MACE [HR 0.62 (95%CI 0.54–0.71)] during long-term follow-up.